Act Of Settlement By Investigators Against Alleged Adultery - Rifki Wahyudi Haris (Universitas Negeri Gorontalo, 2021)
Abstract: This study aims to determine the resolution by investigators to the alleged adultery. The method used in this study is an empirical or sociological research methodology. This study used a qualitative approach and sampling using Purposive Sampling and used descriptive analysis techniques. The results of this study show that the settlement of suspected criminal acts of adultery in the jurisdiction of the Gorontalo Police is carried out with Preventive Efforts, namely socialization or counseling in each village and village. Then the Gorontalo Police often patrols to order or prevent acts prohibited by law including adultery behavior and the form of repressive efforts carried out by the police or investigators of the Gorontalo Police is through investigations, arrests, investigations, until it reaches the judiciary which is then decided by the judge. The repressive efforts made by the police are based on the preliminary evidence that exists because this adultery case is a complaint that can certainly be dismissed because of the party being harmed or caught by Tanagan. Investigators must be more courageous in providing stricter and more straightforward law enforcement in terms of cracking down on the crime of prostitution or in other words adultery.